Efforts to Optimize the Drug Research Unit in Commanding Narcotics Abuse in the Jurisdiction of the Surabaya Polrestabes - Gunawan, Fadhlan Dwi Kartika (Indonesian Journal of Police Studies, 2024)
This research aims to analyze the efforts of the Narcotics Investigation Unit in combating narcotics abuse within the jurisdiction of Polrestabes Surabaya. This study is motivated by the high rate of narcotics abuse in Indonesia, particularly in Surabaya. It employs a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The theories used in this research are the theory of legal effectiveness and POAC management theory. The theory of legal effectiveness is applied to analyze the effectiveness of the Narcotics Investigation Unit’s efforts in combating narcotics abuse. POAC management theory is used to analyze how the Narcotics Investigation Unit plans, organizes, directs, and controls efforts to combat narcotics abuse. The research findings indicate that the Narcotics Investigation Unit has undertaken various measures in combating narcotics abuse, such as prevention through public outreach and education on the dangers of narcotics, enforcement by arresting and investigating drug dealers and users, and rehabilitation to assist drug addicts in receiving rehabilitation services. However, the efforts of the Narcotics Investigation Unit in combating narcotics abuse are still not optimal. This is due to several factors, such as limited resources, including personnel shortages, lack of equipment, and insufficient budget. Additionally, there is a lack of coordination between the Narcotics Investigation Unit and other related agencies. The high demand for narcotics drives drug dealers to continuously find ways to distribute drugs, making enforcement less effective. This research recommends several actions to enhance the efforts of the Narcotics Investigation Unit in combating narcotics abuse, including increasing resources such as budget and personnel, improving inter-agency coordination, and implementing strict measures to dismantle drug networks completely.